Efficacy of Cyclophosphamide treatment for immunoglobulin G4-related disease with addition of glucocorticoids - Yunyun, Fei; Yu, Chen; Panpan, Zhang; Hua, Chen; Di, Wu; Lidan, Zhao; Linyi, Peng; Li, Wang; Qingjun, Wu; Xuan, Zhang; Yan, Zhao; Xiaofeng, Zeng; et al. (Scientific reports, 2017)
Aim to evaluate the efficacy and safety of glucocorticoid monotherapy vs combination therapy of cyclophosphamide (CYC) for IgG4 related disease (IgG4-RD). 102 newly diagnosed IgG4-RD patients were enrolled and assigned to 2 groups: Group I was prednisone monotherapy (0.5–1.0 mg/kg.d, tapered gradually) and Group II was glucocorticoid and CYC (50–100 mg per day). Patients were assessed at different periods. Primary end point was relapse rate; secondary end points included response, remission rate and adverse effects. 52 patients were in Group I and 50 in Group II. At 1 month, both groups achieved obvious improvement. Accumulated relapse rate during 1 year was 38.5% in Group 1, including 12 cases with clinical relapse and 8 patients manifesting only serological relapse; whereas there was 12.0% of relapse in Group 2, only 1 with clinical relapse and other 5 patients got serological relapse. The mean flare time in Group II was significantly longer than that in Group I. All relapsing patients in Group I were sensitive to immunosuppressants. Most patients involving more than 6 organs in Group I relapsed during 1 year. IgG4 levels of relapse cases were significantly higher than non-relapsing patients at baseline. Bile duct, lacrimal glands and lymph nodes were commonly relapsed organs in Group I.